1998
DOI: 10.1139/f97-285
|View full text |Cite
|
Sign up to set email alerts
|

Effects of surgically and gastrically implanted radio transmitters on swimming performance and predator avoidance of juvenile chinook salmon (Oncorhynchus tshawytscha)

Abstract: Radiotelemetry data are often used to make inferences about an entire study population; therefore, the transmitter attachment method should be the one that least affects the study animal. Juvenile chinook salmon (Oncorhynchus tshawytscha) <120 mm in fork length (FL) with either gastrically or surgically implanted transmitters had significantly lower critical swimming speeds than control fish 1 and 19-23 days after tagging. For fish >120 mm FL, fish with gastric implants swam as well as controls 1 day but… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
211
6

Year Published

2001
2001
2021
2021

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 190 publications
(225 citation statements)
references
References 13 publications
6
211
6
Order By: Relevance
“…However, some transmitters (and other tags) have been found to influence mortality and behaviour (Jepson et al, 2002). For example, predation trials with tagged and untagged juvenile Chinook salmon (Oncorhynchus tshawytscha) revealed a reduced swimming speed and higher susceptibility to predation for fish with surgically implanted transmitters (Adams et al, 1998). However, individual animals are likely to respond differently to the tag itself and the tagging procedure and therefore whenever possible it is necessary that devices be experimentally evaluated in a pilot study before being deployed for tracking (Murray and Fuller, 2000).…”
Section: Juveniles and Adultsmentioning
confidence: 99%
“…However, some transmitters (and other tags) have been found to influence mortality and behaviour (Jepson et al, 2002). For example, predation trials with tagged and untagged juvenile Chinook salmon (Oncorhynchus tshawytscha) revealed a reduced swimming speed and higher susceptibility to predation for fish with surgically implanted transmitters (Adams et al, 1998). However, individual animals are likely to respond differently to the tag itself and the tagging procedure and therefore whenever possible it is necessary that devices be experimentally evaluated in a pilot study before being deployed for tracking (Murray and Fuller, 2000).…”
Section: Juveniles and Adultsmentioning
confidence: 99%
“…Among both field and lab studies, individuals implanted with tags generally represent a range of sizes similar to the range of the population from which they were sampled and may represent an age-class of fish such as yearling or subyearling Chinook salmon (for example, [6,8,21]). Analyses thus estimate tag effects for the entire group of fish but do not provide insight as to whether some of the smaller fish within a group experience greater tag effects than larger members of the group.…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies demonstrated that implanting juvenile salmonids with transmitters representing up to 12% of body weight did not affect the swimming performance of fish (Adams et al 1998;Brown et al 1999;Robertson et al 2003;Lacroix et al 2004). However, it has been suggested that the presence of a trailing whip antenna may sometimes cause changes in social status (Connors et al 2002), predator avoidance (Adams et al 1998) and a significant decrease in swimming performance, if its length reaches 300 mm (Murchie et al 2004). In this study, in order to minimize the potential effect of the tag on parr behavior, the transmitters represented a maximum of 3.8% of the body mass and the trailing antenna measured 210 mm.…”
Section: Discussionmentioning
confidence: 99%